2014
DOI: 10.1071/an13092
|View full text |Cite
|
Sign up to set email alerts
|

Energy requirements for maintenance and growth of entire male Bali cattle in East Timor

Abstract: The metabolisable energy (ME) requirements for maintenance and growth of entire male Bali cattle (Bos javanicus) were determined by regressing liveweight change on ME intake. Cattle were fed either a diet (DM basis) of 52.5% urea-treated rice straw plus 47.5% fresh leucaena forage (Expt 1), or fresh leucaena forage alone (Expt 2). In each experiment, liveweight change and feed intake were measured over 4 weeks, after a 1-week introductory period, and feed constituent digestibilities were measured during the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Maintenance energy requirement should be independent of the animal’s production state and nutritional levels, and therefore, it should be related to animal characteristics only [3]. Furthermore, the energy requirement for maintenance is an important part of net energy (NE) system, and accuracy of estimation of the energy requirements for maintenance will influence the absolute NE value of a feed ingredient [46].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Maintenance energy requirement should be independent of the animal’s production state and nutritional levels, and therefore, it should be related to animal characteristics only [3]. Furthermore, the energy requirement for maintenance is an important part of net energy (NE) system, and accuracy of estimation of the energy requirements for maintenance will influence the absolute NE value of a feed ingredient [46].…”
Section: Introductionmentioning
confidence: 99%
“…Energy requirements for maintenance can be estimated us ing body weight (BW) gain as an indirect index of energy retention by the regression analysis method [4,5]. Yuliarty et al [6] reported that metabolizable energy requirements for maintenance (ME m ) of entire male Bali cattle in East Timor determined by regressing BW change against metabolizable energy intake (MEI). Compared to the method of determination the heat leaving the animal’s body, one advantage of this method is that the measurement of BW can be very precise [7].…”
Section: Introductionmentioning
confidence: 99%
“…This value was estimated by regression of estimated ME intake against LWG of Bali cattle across a range of diets typically found in tropical regions that were variable for digestibility, and estimated ME and CP contents. This value is higher than the 0.40 MJ ME/kg LW 0.75 .day reported by Yuliaty et al (2014) to be required to maintain LW of growing Bali cattle. The estimate of ME required to maintain LW of Bali cattle in the present study is within the range of values reported for Bos indicus and Bos taurus cattle elsewhere (Solis et al 1988;Tangjitwattanachai et al 2009;Cardenas-Medina et al 2010); however, the data suggest that this class of Bali cattle may have a lower efficiency of use of ME for LWG than other cattle species.…”
Section: Discussionmentioning
confidence: 56%
“…Bali cattle in Timor Leste were estimated to require 0.40-0.42 MJ ME/kg LW 0.75 . day for maintenance of LW and 39.2 MJ ME/kg LWG (Yuliaty et al 2014). These values were derived from a limited dataset and assume that the efficiency of use of dietary ME does not vary with diet quality.…”
Section: Introductionmentioning
confidence: 99%